Preparation and Characterization of Ultrafine SnO2 Nanoparticles as Anode Materials in Lithium Ion Batteries - Dinh Trong, Le; Ky, Nguyen Van; Hieu, Nguyen Si (VNU Journal of Science: Mathematics - Physics; Vol 39 No 2DO - 10.25073/2588-1124/vnumap.4780, 2023)
In this work, ultrafine SnO 2 nanoparticles were prepared by a facile solvothermal route using SnCl 4 .5H 2 O as initial materials. Phase compositions and microstructures of as-prepared nanoparticles have been investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), and the particle size analyzer. It was found that the obtained ultrafine SnO 2 nanoparticles with the good dispersibility exhibited a pure rutile structural phase with an average crystal grain size of 7.4 nm. The electrochemical performance was characterized by cyclic voltammetry, galvanostatic cycling, and electrochemical impedance spectroscopy (EIS). The galvanostatic cycling results at a current density of 100 mAh . g -1 showed that as-prepared SnO 2 nanoparticles possess a high specific discharge capacity of 1379 mAh∙g -1 with a Coulombic efficiency of 57% at the first cycle, this efficiency was over 91% after the 5 th cycle, and the specific discharge capacity of 276 mAh∙g -1 was maintained during the 50 th cycle of discharge/charge. Despite the relatively low cyclic stability, the effectve electrochemical performance of the SnO 2 electrode due to its ultrafine nanostructure expanded active regions and promoted the reversible process of lithium insertion/extraction.